Promoting Self Employment Among the Unemployed in Hungary and Poland - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 1999)
To evaluate the effectiveness of self-employment assistance to the unemployed in Hungary and Poland more than 5,500 follow-up interviews were conducted in early 1997 by employees of local labor offices with persons in self-employment participant and comparison group samples. Wide ranging differences were observed between the demographic composition of self- employment samples and the general population of unemployed. Program effects were therefore computed as net impact estimates controlling for systematic sample selection using observable characteristics including information on job search assistance from the employment service. While self-employment assistance yielded a favorable set of net impact estimates in both countries, there was a significant dead weight in the operation of programs. Many of those receiving self- employment assistance probably would have gained reemployment without government assistance. However, even after accounting for sample selection, program impacts in both countries on unemployment compensation savings were large, and impacts on employment outcomes were large and positive. In Poland there were also large and positive earnings impacts. A negative estimated earnings impact in Hungary may have been due to a reluctance for full disclosure to tax authorities. In both countries there were appreciable secondary employment effects of between 0.31 and 0.83 additional workers hired per person given self-employment assistance. Among subgroups, self- employment appeared to be more effective in high unemployment areas in Hungary, among females in Poland, outside of service industries in Hungary, and outside of manufacturing and construction in Poland.
Keywords: J0; J6; 330; unemployment; labor; market; programs; self-employment; Hungary; Poland; O'Leary